TEACHER ORAL CORRECTIVE FEEDBACK IN A NON-FORMAL ADULT EFL CONVERSATION CLASS - Subekti, Eri (2016)
This study investigates the teacher oral corrective feedback in a non-formal conversation class of EFL adult learner context in Indonesia. The study aims at finding out the types of oral corrective feedback that employed by the teacher and how the teacher implement the oral corrective feedback to adult students. The study was conducted in a private conversation class of an English course in Bandung. The course provides private conversation classes mostly for adult learners with private teaching method. The participants were one non-native English teacher and three adult private students. This study mainly employs a qualitative research design, embracing the characteristics of a case study. The data were collected through observation and stimulated recall interview. The observation was done twelve times for each student to capture the types of teacher's corrective feedback and the uptake that might come up following different types of oral corrective feedback. The data consists of thirty six hours of interaction between the English teacher and the students. The interactions were recorded and transcribed, and then coded according to the categorization of oral corrective feedback models by Lyster and Ranta (1997) and Ellis (2009). The data were also obtained from stimulated recall interview to confirm the data findings gained from observation and reveal the teacher's comments on employing different types of corrective feedback. The result shows that teacher used all types of corrective feedback with recast as the most frequent type of oral corrective feedback that was used by the teacher in teaching the adult students. In implementing the oral corrective feedback to adult students, the teacher mainly paid attention on three types of error (grammatical, lexical, and phonological) with the most frequent attention on grammatical error and the most tolerant one on phonological error. Regarding the uptake, it was found that each corrective feedback had different effect on the students' uptake. The effect can be seen in the number of repairs as the sign that the students successfully responded to the teacher's oral corrective feedback. It was also found that the teacher tends to be instinctively in giving corrective feedback as spontaneous correction.;---Penelitian ini membahas tentang teacher oral corrective feedback pada kelas EFL conversation siswa dewasa di Indonesia. Penelitian ini bertujuan untuk mengetahui tipe-tipe oral corrective feedback yang digunakan oleh guru dan bagaimana guru tersebut menngimplementasikan oral corrective feedback pada siswa dewasa. Penelitian ini dilakukan di sebuah kelas conversation pada sebuah kursus privat Bahasa Inggris di Bandung. Kursus tersebut menyediakan kelas conversation terutama untuk siswa dewasa dengan metode privat. Partisipan pada penelitian ini terdiri dari seorang guru dan tiga siswa dewasa. Penelitian ini menggunakan metode kualitatif dengan karakteristik studi kasus. Teknik pengumpulan data dilakukan melalui observasi dan stimulated recall interview. Observasi dilakukan sebanyak dua belas kali pada setiap siswa untuk mengetahui tipe corrective feedback yang digunakan oleh guru dan uptake yang muncul setelahnya. Data terdiri dari tiga puluh enam jam interaksi antara guru dan siswa. Interaksi tersebut direkam dan ditranskrip, kemudian dikelompokkan berdasarkan model kategori oral corrective feedback oleh Lyster dan Ranta (1997) dan Ellis (2009). Data juga diambil melalui stimulated recall interview untuk mengkonfirmasi data hasil observasi serta komentar guru tentang penggunaan tipe oral corrective feedback yang berbeda. Hasil penelitian ini menunjukkan bahwa guru menggunakan semua tipe oral corrective feedback dengan recast sebagai tipe yang paling sering digunakan oleh guru ketika mengajar siswa dewasa. Dalam mengimplementasikan oral corrective feedback pada siswa dewasa, guru menitikberatkan pada tiga jenis error (grammatical, lexical, phonological) dengan perhatian terbesar pada grammatical error dan terkecil pada phonological error. Kaitannya dengan uptake, ditemukan bahwa setiap corrective feedback memiliki efek yang berbeda pada uptake siswa. Efeknya dapat dilihat pada jumlah repair yang merupakan tanda bahwa siswa telah berhasil merespon oral corrective feedback yang diberikan oleh guru. Ditemukan pula bahwa guru cenderung memberikan oral corrective feedback berdasarkan insting sebagai koreksi yang spontan.